Family Stability Among Families of Children with Autism Disorder: A Social Study (An Applied Study on Families of Children with Autism Disorder in the Regions of the Kingdom of Saudi Arabia – 2023 / 1444 AH) - Almalki, Albatool Houmeid; Alkhaldi, Ryouf Nasser; Alqahtani, Rajaa Taha (Journal of Humanities & Social Sciences, 2025)
This study aims to analyze the effects of having a child with autism disorder on family stability within Saudi society. The study relied on a descriptive analytical approach using data collection tools, including questionnaires and semi-structured interviews. The sample included 170 parents of children with autism, in addition to conducting 8 interviews. The results showed increased levels of psychological and social stress among families, especially mothers, which reflected on the stability of family life and increased tension in marital and educational relationships. The findings also indicated that the availability of psychological and social support contributes to improving family adaptation and reducing problems. The study recommends conducting further research that highlights the positive effects on the family. It also emphasizes the importance of strengthening family counseling and distributing responsibilities among family members, in addition to raising community awareness about autism disorder through media and awareness programs. Furthermore, the study urges achieving balance in the treatment of children to avoid their feelings of insecurity within the family.